The Impact of Using the international standard for Training (ISO-10015) to Improve the Quality of the Control Activity – A Survey Study at the Federal Board of Supreme Audit. - كبرو رغد يوسف; حسون عصام خيون (Journal of Economics and Administrative Sciences, 2018)
The great importance of training made it as an investment for the organization, and assert the Quality of performance which support it by prepare the employee to the Current and future Jobs . The Research problem a rounded about How to measure the impact of training based on (ISO 10015) and its effect on the Quality of performance , How to evaluation the results of training to attained the training goals . The Research aims to find out the effects of application of international standard guidelines (ISO 10015) to attained the quality of audit work achieved in the Federal Board of Supreme Audit. The Research sought to achieve a number of objectives cognitive and applied on the basis of four key assumptions, and other sub. Has been used a questionnaire -mainly- in the collection of data and information on the research , as were distributed as a sample of (110) employee by analyzing the answers of leadership in the Office of Financial Supervision Federal Top Managers and their assistants, experts, coordinating Managers, heads of departments, presidents of boards in the financial controlling , by using an appropriate measures and statistical tools to reach the results The research concluded the results of analytical vindicated assumptions mentioned above the existence of effect of international standard (ISO 10015) in the quality of audit work, as well as having a medium level of application specifications, and the presence of the conclusions, and submitted its recommendations of Research model; to achieve quality performance for the organization and employee